Terapia ocupacional social, juventudes e espaço público - Silva, Marina Jorge da (2019)
A socio-historical analysis of social recognition of the youth showed that there is a dispute process for this population to achieve visibility and effective possibilities to exercise citizenship and participate in public life. However, this analysis identified that a significant part of the Brazilian youth, such as the poor youth, still lacks the conditions essential to their social integration. Based on Hannah Arendt’s propositions, there is an inseparable link between the social recognition of a group as a political actor, the realization of its citizenship, and its visibility and inclusion in the public space. Therefore, thinking and acting on the restriction to citizenship of socially vulnerable and invisible individuals or collectives necessarily involve a dialogue with the public space. Based on these principles, this study aimed to identify whether the actions conducted for over a decade by the METUIA/UFSCar team (an inter-institutional group of studies, training and actions in social occupational therapy), in the form of university extension, research, and undergraduate and graduate teaching activities, with poor urban youths specifically through a project developed in a neighborhood in the outskirts of the municipality of São Carlos, state of São Paulo, Brazil, have somehow changed the relationship that these young people have with the public spaces in their neighborhood and city. Based on case studies, along the lines of the Social Sciences, three data collection strategies were articulated: reading and analysis of the studies produced by the METUIA/UFSCar team on the experience in question, participative objectification of the Workshops on activities, dynamics and projects developed in this neighborhood throughout 2017, and interviews with five young people. The data were analyzed and discussed based on the notion of public space developed by Hannah Arendt considering the four elements that she highlighted as essential constituents of the public space: visibility, plurality, equality and freedom. Actions in social occupational therapy shed light on the socially vulnerable population investigated, the poor youth in this case, on its needs and demands, favoring visibility before the municipal government and other generational groups inside and outside its living territory. In addition, through technical and professional work in social occupational therapy, life-sharing spaces have been promoted with the aim of fostering human plurality and sociability, discussing the production of respect for diversity, and coping with situations of inequality and conflicts arising from encounters with difference. Nevertheless, occupational therapy interventions are evidently insufficient to tackle the macro-structural conditions that stand in the way of experimenting with the possibility of enjoying equality and freedom to participate in collective life. In spite of that, it is concluded that social occupational therapy can modify the relationship between youths and the public spaces, including individuals and voices in this scene plurally and with visibility, and that occupational therapists are possible actors in the mediation, articulation and promotion of experiences in public and collective life.